Analisis Integrasi Dinamis Pasar Modal Indonesia terhadap Pasar Modal ASEAN Pasca Berlakunya Masyarakat Ekonomi ASEAN - Nia, Wa; Ma’mun, Sitti Zakiah; Maksar, Muhammad Sofian (J-MAS (Jurnal Manajemen dan Sains), 2024)
This research intends to understand the dynamic integration of the Indonesian capital market with the ASEAN Capital Market before and after the implementation of the MEA (ASEAN Economic Community) or AEC. The sample used in this observation is a series of data collected in the period January 2011 to December 2015 before the MEA was implemented and January 2016 to December 2022 after the MEA was implemented, while the capital markets studied were the Indonesian Stock Exchange, Kuala Lumpur Stock Exchange, Stock Exchange Singapore, Philippine Stock Exchange and Thai Stock Exchange. This research analyzes the dynamic integration of the Indonesian capital market towards ASEAN after the implementation of the MEA using the Orthogonal Generalized Autoregressive Conditional Heteroscedasticity (OGARCH) method which can manifest the level of integration in a measurable way. The results of this research are that there is co-movement among the ASEAN capital markets studied, however, not all ASEAN capital markets are fully integrated. The results of this observation also found that the Indonesian Stock Exchange, Kuala Lumpur Stock Exchange, Thailand Stock Exchange and Singapore Stock Exchange were integrated but the Philippine Stock Exchange was not. The Philippine Stock Exchange tends to be segmented rather than integrated.